2005
DOI: 10.1177/0092070304269953
|View full text |Cite
|
Sign up to set email alerts
|

Customers' Reactions to Price Increases: Do Customer Satisfaction and Perceived Motive Fairness Matter?

Abstract: Most of the previous research on price changes has focused on price decreases. This article investigates the effects of price increases at an individual level. The authors argue that customers’ reactions to price increases (i.e., re-purchase intentions) are strongly driven by two factors: the magnitude of the price increase and the perceived fairness of the motive for the price increase. In this context, the authors examine the role of customer satisfaction in influencing the impact of these two variables on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
2
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 56 publications
6
160
2
13
Order By: Relevance
“…Furthermore, not only do we highlight the direct impact of unfairness on intention to repurchase, but we also demonstrate the significance of trust and satisfaction as mediators. The examination of a mediating role of trust and satisfaction expands knowledge in this research area, since the role of trust in the relationship between fairness perceptions and repurchase intentions remains under-investigated (Santos and Basso, 2012), while fairness and satisfaction have mainly been studied in isolation (Homburg et al, 2005). Moreover, little research focuses on the consequences of offering different prices to prospective as opposed to current customers taking both perspectives into consideration (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, not only do we highlight the direct impact of unfairness on intention to repurchase, but we also demonstrate the significance of trust and satisfaction as mediators. The examination of a mediating role of trust and satisfaction expands knowledge in this research area, since the role of trust in the relationship between fairness perceptions and repurchase intentions remains under-investigated (Santos and Basso, 2012), while fairness and satisfaction have mainly been studied in isolation (Homburg et al, 2005). Moreover, little research focuses on the consequences of offering different prices to prospective as opposed to current customers taking both perspectives into consideration (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Price-disadvantaged buyers view differential pricing tactics as unfair, and they subsequently express lower repurchase intentions , avoid transactions or do not buy at all (Cockrill and Goode, 2010). Moreover, Homburg et al (2005) found a direct link between perceived fairness and intention to repurchase. Therefore, customers' perception of fairness of a retailer's action can affect customer retention (Chebat and Slusarczyk, 2003).…”
Section: Outcomes Of Unfairness Perceptionmentioning
confidence: 88%
See 1 more Smart Citation
“…Thereafter, customer satisfaction occurs when the performance of a product or service meets or exceeds the customer's expectations (Oliver, 1980). In this research, we follow this performance-focused conceptualization of satisfaction, under which price is not included as part of the satisfaction judgment (Homburg et al, 2005a). We further take on a cumulative perspective, which is based on repeat purchases, of satisfaction because it better explains loyalty behavior than transaction-specific satisfaction, which is based on a single experience (Olsen and Johnson, 2003).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…As a result, marketing scholars have increasingly focused on relationships and brands, thus neglecting the role of price perception in the management of customer satisfaction and customer loyalty (Steiner et al, 2013;Varki and Colgate, 2001). However, price still plays a considerable role even for branded products because it may have a stronger influence on consumers' assessment of a brand than quality (Voss et al, 1998) and it is directly linked to profitability (Homburg et al, 2005a). Hence, an important field of marketing has remained vastly untapped in relationship marketing (Varki and Colgate, 2001;Steiner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%